2011
DOI: 10.2214/ajr.10.5350
|View full text |Cite
|
Sign up to set email alerts
|

T2* Measurements of 3-T MRI With Ultrashort TEs: Capabilities of Pulmonary Function Assessment and Clinical Stage Classification in Smokers

Abstract: MRI with ultrashort TEs is potentially as useful as quantitatively assessed MDCT for pulmonary function loss assessment and clinical stage classification of COPD in smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
95
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(107 citation statements)
references
References 30 publications
11
95
1
Order By: Relevance
“…Although advances continue with techniques such as ultrashort echo time (UTE) imaging of the lung parenchyma (3), conventional proton-based MRI is at a fundamental disadvantage for pulmonary applications because it cannot directly image the lung airspaces. This disadvantage of proton MRI can be overcome by turning to a gaseous contrast agent, such as the noble gas helium-3 ( 3 He) or xenon-129 ( 129 Xe), which upon inhalation permits direct visualization of lung airspaces in an MR image (48).…”
mentioning
confidence: 99%
“…Although advances continue with techniques such as ultrashort echo time (UTE) imaging of the lung parenchyma (3), conventional proton-based MRI is at a fundamental disadvantage for pulmonary applications because it cannot directly image the lung airspaces. This disadvantage of proton MRI can be overcome by turning to a gaseous contrast agent, such as the noble gas helium-3 ( 3 He) or xenon-129 ( 129 Xe), which upon inhalation permits direct visualization of lung airspaces in an MR image (48).…”
mentioning
confidence: 99%
“…The first studies employing UTE methods reported that the tissue density was related to MR signal 109 and T 2 *. UTE MRI was also used to measure signal intensity and T 2 * in emphysema 110 and showed good correlations with histological measurements while T 2 * correlated with pulmonary function measurements 111 and pulmonary signal intensity was related to tissue density, pulmonary function and CT density measurements. 108 Very recently methods have been developed that exploit optimized 112 and so-called zero echo time (ZTE) 113 approaches and this has resulted in excellent, MR image quality and signal in pulmonary images that is very similar to CT. Another method for measuring regional lung function, involves using inhaled oxygen in combination with 1 H MRI 114 and this exploits the alteration of lung tissue 1 H relaxation times by molecular O 2 .…”
Section: Pulmonary Mri Measurements Of Copdmentioning
confidence: 99%
“…The use of detailed gradient echo signal decays to estimate proton density, and thus lung water content (35), may have important diagnostic implications in a number of diseases, including COPD and cystic fibrosis. Indeed, Ohno et al demonstrated the feasibility of making ultra-short TE gradient echo acquisitions (0.2 ms to 4.7 ms) even at 3 T to measure T 2 * in smokers, potentially offering an assessment of clinical stage classification (22). Theilmann et al stressed the importance of the inflationary state of the lung in making T 2 * and associated lung water density measurements at 1.5 T (21), while Yu et al more recently measured T 2 * in lung parenchyma at 1.5 T and 3 T, pointing out that normal free breathing has a small effect on the T 2 * values compared to the full inspiration/expiration extremes (23).…”
Section: Relaxation Properties Of Lung Tissue From Imaging Studiesmentioning
confidence: 99%